(untitled) (The Pakistan Development Review, 2025)
This study, examines the effect of remittances on healthcare expenditure in Pakistan by utilising the Pakistan Social and Living standards Measurement (PSLM) survey. The total healthcare expenditure is classified into two categories, i.e. expenditure on medicines and expenditure on clinical services. The study analyses these categories in case of both rural and urban areas of the country. Such data is generally characterised by selection bias; therefore, we employ Propensity Score Matching (PSM) instead of the commonly used econometric techniques. Findings of the study indicate that remittances enhance spending on both the clinical services and medicines. This result is robust across the urban and rural areas of Pakistan. The comparison between the clinical services and medicines shows that the impact is higher on clinical services as compared to the impact on medicines. This suggests that remittances help to improve the preventive nature of health outcomes in Pakistan. JEL Classification: D10; I21; O15 Keywords: Remittances, Healthcare Expenditure, Medical Expenditure, Clinical Expenditure, Propensity Score Matching